Just-In-Time Inventory Management Practice and Performance of Selected Polytechnics in Southwest, Nigeria: Implications for Sustainable Stock Efficiency - Gbadamosi, Olaniyi Mufutau; Alase, Peter O.; Ilugbusi, Segun B. (ABUAD Journal of Social and Management Sciences, 2024)
This study examined Just-in-Time (JIT) inventory management practice and performance of selected polytechnics in Southwest Nigeria, and the implications for sustaining stock efficiency. The study used descriptive survey research design and a total of one thousand and thirty-six (1,036) store employees from federal, state and private polytechnics in the Southwest, Nigeria. A sample size of five hundred and forty-four (544) determined through multi-stage and stratified sampling technique was used for data analysis. Primary data were obtained through questionnaire while linear regression was employed to determine the effects and statistical significance of the relationships between the study variables. The Statistical Package for Social Sciences (SPSS) version 24.0 was applied to process the data and the hypothesis was tested at p-value of = 0.05 level of significance while descriptive statistical analysis was used to identify frequencies and percentages. The findings of the study showed that JIT inventory management practice cannot be underestimated in determining performance of polytechnics in Southwest Nigeria. The study recommended that management of polytechnics in Southwest Nigeria should develop a policy framework to facilitate faster implementation of the best inventory management practices such as JIT as it has proven to have significant positive effect on employees’ performance.